UTILIZATION OF ETHANOL FRACTION OF JARUM TUJUH BILAH LEAVES (Pereskia bleo (Kunth) D.C) AS XANTHINE OXIDASE INHIBITOR IN THE FORMATION OF URID ACID - Sarwawan, Ade Putri Hawiyah; Sitorus, Saibun; Gunawan, Rahmat (Jurusan Kimia FMIPA UNMUL, 2019)
This research was conducted to determine the content of secondary metabolite contained in the extract and ethanol fraction of â€œJarum tujuh bilahâ€ leaves (Pereskia bleo (Kunth) DC) and and inhibition of xanthine oxidase activity obtained from the isolation of cow's milk. The xanthine oxidase activity is measured at a wavelength of 290 nm. The results of this research indicate that in the ethanol extract and fraction of â€œjarum tujuh bilahâ€ leaves have the secondary flavonoids, alkaloids and phenolic compounds. The highest inhibition of xanthine oxidase activity in the ethanol extract of â€œjarum tujuh bilahâ€ leaves was 91.67%, while the inhibition of allopurinol was 50% and the ethanol fraction of â€œjarum tujuh bilahâ€ leaves was seven blades by 90%.